Conditions of formation of ferruginous rocks of the Krivoy Rog-Kremenchug zone - Usenko, O. (Geofizicheskiy Zhurnal, 2015)
Variation of lithosphere thickness during formation of the Krivoy Rog series of the Krivoy Rog-Kremenchug suture zone formation has been found. Analysis of rock associations differences of the greenstone structures of the Middle Dnieper megablock of the Ukrainian Shield and the Krivoy Rog suture zone has been conducted. It has been shown that the reason of variability of ferruginous formations is different composition of the fluid interacting with the melt on the roof of partial melting layer. Before 2.8 Ga the influence of neutral aquatic fluids and weakly acid ones with chlorine was essential. After 2.8 Ga the total amount of water dissolved in the mantle melts decreases and activity of alkaline fluids with fluorine was manifested as well. It resulted in oxidation-reduction processes and subsequent subdivision into unmixed phases. These processes are related to evolution of deep layers of the Earth.